Productivity spillovers from services firms in low- and middle-income countries: What is the role of firm characteristics and services liberalization? - Deborah Winkler (Asian Development Bank Institute (ADBI), 2018)
Using a cross-section of more than 38,000 manufacturing and 24,000 services firms in 105 low- and middle-income countries from the World Bank's Enterprise Surveys, this chapter assesses whether there are productivity spillovers from services to manufacturing firms located in the same subnational region. The chapter confirms positive spillovers resulting from a higher average regional productivity and technology intensity of services firms, but rejects the existence of spillovers from services firm presence alone. It also finds that the extent of the spillovers depends on a country's income status and a manufacturing firm's absorptive capacity, including its services intensity, firm size, foreign ownership status and exporting behavior. The chapter then analyzes the characteristics of services firms with higher productivity and technology intensity as these determine the services' spillover potential. Foreign ownership status and the top manager's experience are positively associated with a services firm's output per worker and technology intensity, while exporting status only shows a positive correlation with technology intensity. Finally, the chapter examines whether services liberalization mediates productivity spillovers from services to manufacturing firms in a region. Using the World Bank's Services Trade Restrictions database, the results suggest that lower regulations in mode 1 and mode 3 services trade increase spillovers from services firms to manufacturing firms via a productivity-enhancing effect in the services sector.
Keywords: F1; F2; 330; services firms; productivity spillovers; technology; absorptive capacity; services liberalization